Curriculum reform: a transformation or consumption model for politics and international relations?. Issue 3 (2nd July 2016) - Engel, Susan
ABSTRACT: For decades, politics and international relations (PaIR) programs across Australia have taken a smorgasbord or student consumption approach to curriculum development. This article examines whether, with the Australian Qualifications Framework (AQF), there has been a systematisation and transformation of curriculum. It surveys 21 programs and majors in the field offered at 10 universities. It analyses directions in program structure, content and to a lesser extent delivery in order to discover whether there is a shared picture of graduate outcomes. The model of curriculum as a product students' select elements of to consume has largely continued and there has been no disciplinary debate about direction. This may well result in marginalisation if PaIR cannot successfully attract enough new students or influence regulatory debates, which will likely expand given the ongoing massification of higher education in Australia.